Перспективи застосування медіації як способу врегулювання сімейно-правових спорів - Дутко, Альона; Dutko, Alyona (Видавництво Львівської політехніки, 2020)
Наголошено на необхідності впровадження примирних процедур, позасудових та досудових способів врегулювання спорів, які дозволять знизити навантаження на суддів і підвищити якість здійснення правосуддя. Пропонується широке впровадження процедури медіації як механізму реалізації положень законів, що передбачають можливість примирення сторін. Аналізується медіація як спосіб врегулювання сімейноправового спору. Автор визначає поняття та види сімейно-правового спору.

The article emphasizes the need to introduce conciliation procedures, out-of-court and pre-trial methods of dispute resolution, which will reduce the burden on judges and improve the quality of justice.It is proposed that the mediation procedure be widely introduced as a mechanism for implementing the provisions of laws providing for the possibility of reconciliation between the parties. Mediation is analyzed as a way to resolve a family legal dispute. The author defines the concept and types of family law dispute.
Prospects for the use of mediation as a method of settlement of family legal disputes
Keywords: медіація; сімейно-правовий спір; форма захисту права; спосіб захисту права; врегулювання спору за участю судді; mediation; family law dispute; form of protection of the law; method of protecting of the law; dispute settlement with the participation of a judge; 347.995